Immigration, the Borderlands, and the Resilient Homeland - Shaw-Taylor, Yoku (Bernan Press, 2023)
This title combines original research, case studies, and synoptic analysis to cover highly charged topics in America today. Each chapter in this edited volume offers conditional responses to three essential questions about the disciplinary status of homeland security: What are the domain’s central problems? What research methods are best able to address those problems? What has research contributed to addressing homeland security’s core problems? The volume is divided into two main sections. Part I: Immigration and Management covers topics such as: Immigration enforcement Illegal crossing Border security Gaps in securing the borderland Part II: The Resilient Homeland addresses issues such as Lessons learned from the pandemic Disaster recovery and preparedness Public health Cybersecurity This publication bridges knowledge from various topics related to homeland security into one volume.